Development of the scale of project based virtual learning qualifications - Tuncer, Murat; Yilmaz, Ömer (Ankara University, 2013)
The purpose of this study is to develop a reliable and valid scale to determine project based virtual learning qualifications. Project based virtual learning competencies as a new skill can be defined as emerging developing technology qualifications. The sample of study consisted of 466 teacher candidates at the education faculty of Firat University. In order to test the status of the structure of the scale which was created according to the results of the exploratory factor analysis, the confirmatory factor analysis has been used. According to the results of confirmatory factor analysis, SRMR value of the scale of PBVLQ has been found as,046, RMSEA value as,048, GFI value as,925 and AGFI value as,904. According to these compliance index values, the scale development process is successful. In addition, Cronbach's Alpha coefficient for the overall scale has been calculated as,864. In the light of these findings it can be said that the scale is reliable and valid.
Proje tabanlı sanal ö?renme yeterlikleri (PTSÖY) ölçe?inin geliştirilmesi
Keywords: Factor analysis; Project based learning; Project based virtual learning; Scale development; Virtual learning